Social capital, innovation and entrepreneurial orientation in SME companies : a study on ICT Clusters in Brazil and Spain - Nofal, Rose (2021)
Dissertação (mestrado)—Universidade de Brasília, Faculdade de Economia, Administração e Contabilidade, Programa de Pós-Graduação em Administração, 2021.